Improvement of fixed offshore platforms' boat landing performance using practicable design criteria - Hamadelnil, A. (Society of Petroleum Engineers, 2017)
Boat landings on fixed offshore platforms are designed to absorb the impact energy from the boats approaching the platform for crew transfer. As the size and speed of operating boats vary, the design and maintenance of the boat landings become more challenging. Different oil and gas operators adopt different design criteria for the boat landing design in the region of South East Asia. Rubber strip is used to increase the capacity of the boat landing in absorbing bigger impact energy. Recently, it has been reported that all the rubber strips peel off the boat landing frame within one to two years and replacement is required to avoid puncturing of the boat's hull by the exposed sharp edges and bolts used to secure the rubber strip. The capacity of the boat landing in absorbing the impact energy is reduced after the failure of the rubber strip and hence results in failure of the steel members. The replacement of the rubber strip is costly as it requires diving spread. The objective of this study is to propose the most practicable criteria to be adopted by oil and gas operators in the design of the boat landings in the region of South East Asia to improve the performance of the boat landing and to assure safe operation and cheaper maintenance. This study explores the current design and maintenance challenges of boat landing and compares the criteria adopted by different operators. In addition, this study explains the reasons behind the denting of the boat landing. It also evaluates the effect of grout and the rubber strip in the capacity of the boat landing. Boat landing model and analysis using USFOS and SACS software are carried out and presented in this study considering different design criteria. This study proposes the most effective and practicable criteria to be used in designing the boat landing in South East Asia region to achieve better performance, safe operation and less cost for maintenance. Copyright © 2017 by the International Society of Offshore and Polar Engineers (ISOPE).